Pengaruh Keteladanan Guru Pendidikan Agama Kristen terhadap Karakter Peserta Didik Kelas X SMK Negeri 1 Raya Kabupaten Simalungun Tahun Pembelajaran 2023/2024 - Marice Simamora; Johari Manik; Hasudungan Simatupang; Sandy Ariawan; Ordekoria Saragih (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The purpose of this study was to determine the positive and significant influence of the Exemplary Christian Education Teacher on the Character of Class X Students of SMK Negeri 1 Raya, Simalungun Regency in the 2023/2024 Academic Year. The research method used was a quantitative method with descriptive statistics. The population was 159 Protestant Christian students of class X of SMK Negeri 1 Raya, Simalungun Regency in the 2023/2024 Academic Year and a sample of 40 people was determined using a random sampling technique. Data were collected using a positive closed questionnaire of 39 items, namely 20 items for variable X and 19 items for variable Y. The results of the data analysis showed that there was a positive and significant influence of the Exemplary Christian Religious Education Teachers on the Character of Class X Students of SMK Negeri 1 Raya, Simalungun Regency in the 2023/2024 Academic Year, as evidenced by the following data analysis: 1) Analysis requirements test: a) Positive relationship test obtained rxy value = 0.479> rtable ( = 0.05, n = 40) = 0.312. b) Significant relationship test obtained tcount = 3.364> ttable ( = 0.05, dk = n-2 = 38) = 2.021. 2) Influence test: a) Regression equation test Y ̂=